APC controls asymmetric Wnt/β-catenin signaling and cardiomyocyte proliferation gradient in the heart. (December 2015) - Ye, Bo; Hou, Ning; Xiao, Lu; Xu, Yifan; Boyer, James; Xu, Haodong; Li, Faqian
Abstract: Aims: Cardiomyocyte (CM) proliferation increases from the inner trabecular to outer compact myocardium in fetal hearts. We determined if canonical Wnt signaling has directional and graded activity to maintain this CM proliferation gradient. Moreover, we investigated whether perturbation of Wnt signaling intensity could modulate CM proliferative activity. Methods and results: With confocal microscopy and image analysis we found that the Wnt effector, β-catenin, formed a signaling gradient which positively correlated with CM proliferative activity across ventricular walls of wild type (WT) embryos at embryonic day (E) 13.5 and 17.5. Negative Wnt regulators, adenomatosis polyposis coli (APC), had a reverse distribution pattern. The activation of canonical Wnt/β-catenin signaling by deletion of Apc in CMs led to ventricular hyperplasia with no adverse effects on fetal survival or CM differentiation. In contrast, cardiac deletion of β-catenin resulted in ventricular hypoplasia and fetal demise by E14.5. We further revealed differential distribution and regulation of three cyclin Ds in fetal hearts. Cyclin D1 was mainly expressed in endothelial cells. Although both cyclin D2 and D3 were present in CMs, only cyclin D2 was regulated by Wnt signaling perturbation: downregulation by β-catenin deletion and upregulation by Apc knockout. Conclusion: Canonical Wnt signaling is asymmetrical and graded across ventricular walls and positively regulates CM proliferation via cyclin D2. Graphical abstract: Highlights: β-cat played a critical role in maintaining CM proliferation gradient. APC formed an intensity gradient opposite to β-cat and CM proliferative activity. With Apc/β-cat double cKO, we found that Wnt signaling regulated cyclin D2.